“Woord van God, Woord van die lewe”? Op weg na ’n verantwoordelike teologiese hermeneutiek - Smit, D. J. (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
The paper is an edited version of a public address at the opening of the Theology Faculty of the Stellenbosch University on the 3rd February 2008. It deals with the confessional language used by the church to describe the work and effects of the Holy Scriptures in the church. Arguing that such an approach is not completely unknown in the Reformed tradition, where for example Bavinck and Berkouwer made contributions of this nature, the paper provides a brief overview of some of the popular descriptions (which could be called speech-acts in contemporary language) of the role of Scripture in the life of faith. Reflecting on such descriptions, a brief discussion is focused on the question what the implications could be for so-called responsible hermeneutics in the life of the church.